Elevated serum cortisol levels and associated factors among postpartum mothers in Mbarara district, rural south western Uganda - Catherine Atuhaire; Taseera Kabanda; Daniel Atwine; Godfrey Zari Rukundo; Judith Byaruhanga; Samuel Maling; Francis Bajunirwe (Discover Medicine, 2025)
Background: Serum cortisol is often elevated in postpartum mothers, but data on its prevalence and associated factors remain limited in many settings. The current study aimed at examining the factors associated with elevated serum cortisol levels among postpartum mothers in Mbarara district, rural southwestern Uganda. Methods: We conducted a facility based cross sectional study among mothers between 6 weeks and 6 months after childbirth. Using consecutive sampling, mothers were enrolled from postnatal clinics of two health facilities, Mbarara Regional Referral Hospital and Bwizibwera Health Center IV, a county level health facility in rural southwestern Uganda. The blood cortisol levels were measured using a chemiluminescence with the use of a standard, commercially available competitive immunoassay (Diagnostic Products Corp. Nichols Institute Diagnostics, San Juan Capistrano, CA). Postpartum depression (PPD) was diagnosed using the Mini International Neuropsychiatric Interview (MINI) version 7.0.2, based on the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM-5) criteria. Results: We enrolled 309 postpartum mothers, and the prevalence of elevated serum cortisol levels was 26.2% (95% CI 22.0–31.4). Elevated serum cortisol levels were significantly associated with PPD (AOR = 2.9, 95% CI 1.6–5.3, p < 0.001), health facility level attended by the mother (AOR = 3.8, 95% CI 1.9–7.6, p = 0.001), pre-diabetes (AOR = 2.5, 95% CI 1.3–5.0, p = 0.008) and diabetes mellitus status (AOR = 4.0, 95% CI 1.8–8.9, p = 0.001), and decreased involvement in physical activity (AOR = 0.3, 95% CI 0.1–0.7, p = 0.002). Conclusion: In this study of elevated serum cortisol levels was significantly associated with postpartum depression, attending a rural healthcare facility, having pre-diabetes or diabetes mellitus status, and reduced physical activity. These findings underscore the need for targeted holistic interventions addressing both physical and mental health challenges in postpartum women
Keywords: Serum cortisol; Postpartum depression; Physical activity; Diabetes mellitus; Rural Uganda